Fine-scale Beta-diversity Patterns Across Multiple Arthropod Taxa Over a Neotropical Latitudinal Gradient - Gonçalves-Souza, Thiago; Araújo, Marcel S. [UNESP]; Barbosa, Eduardo P.; Lopes, Sonia M.; Kaminski, Lucas A.; Shimizu, Gustavo H.; Santos, Adalberto J.; Romero, Gustavo Q. (Wiley, 2015)
Documenting how diversity patterns vary at fine- and broad scales may help answer many questions in theoretical and applied ecology. However, studies tend to compare diversity patterns at the same scale and within the same taxonomic group, which limits the applicability and generality of the results. Here, we have investigated whether vegetation-dwelling arthropods from different trophic ranks and with distinct life histories (i.e., ants, caterpillars, cockroaches, and spiders) have different beta-diversity patterns at multiple scales. Specifically, we compared their beta diversity across architecturally distinct plant species (fine-scale process) and a latitudinal gradient of sites (broad-scale process) along 2040 km of coastal restinga vegetation in the Neotropics. Over 50 percent of the compositional changes (β-diversity) in ants, caterpillars, and spiders and 41 percent of those in cockroaches were explained by plant identity within each site. Even groups that do not feed on plant tissues, such as omnivores and predators, were strongly affected by plant identity. Fine-scale variation was more important than large-scale processes for all studied groups. Performing a cross-scale comparison of diversity patterns of groups with distinct life histories helps elucidate how processes that act at regional scales, such as dispersal, interact with local processes to assemble arthropod communities.
Keywords: Alpha, beta, and gamma diversity; Dispersal; Diversity partitioning; Life history; Plant identity